INTEGRASI TEKNOLOGI DAN KURIKULUM DALAM PENDIDIKAN: ANALISIS TREN DAN INOVASI TERKINI: INTEGRATION OF TECHNOLOGY AND CURRICULUM IN EDUCATION: AN ANALYSIS OF RECENT TRENDS AND INNOVATIONS - Fathurrahman, Muhammad; Ismail Djakaria; Sarira, Regina Amelia (KAMBIK: Journal of Mathematics Education, 2024)
This bibliometric analysis investigates trends in publications linking "technology" with "curriculum" over the past five years, focusing on how technology is integrated into the educational curriculum. Utilizing the Dimensions database and VOSviewer visualization tool, this study successfully identified four main clusters: theoretical concepts, practical implementation, technological innovations, and health education. The research findings indicate a need for a curriculum that is flexible and comprehensive and effectively prepares students with academic knowledge, practical skills, and technological abilities to navigate an uncertain future. Moreover, this study highlights the significance of collaboration between educational institutions and the industry sector to maintain the curriculum's relevance to the changing needs of the global job market and ensure students acquire the necessary skills to succeed.